INHIBITORY POWER TEST OF N-HEXANE EXTRACT OF MALAKA LEAVES (Phyllanthus emblica) ON GROWTH Microsporum canisIN-VITRO - Miranda, Lola Almira; Asmilia, Nuzul; Fakhrurrazi, Fakhrurrazi; Rusli, Rusli; Amiruddin, Amiruddin; Jalaluddin, M. (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: Malacca leaves are one of the medical plants that can be used in traditional medicine. Malacca leaves contain several active compounds that can be effective in inhibiting fungal growth. This study aims to investigate the inhibition of n-hexane Malacca leaves extract on Microsporum canis growth in vitro.Materials and Methods: The method used in this study is Kirby-Bauer disc diffusion with 5 treatments, namely P1 (25% Malacca leaves n-hexane extract), P2 (50% Malacca leaves n-hexane extract), P3 (75% Malacca leaves n-hexane extract), P4 (control (+): ketoconazole) and P5 (control (-): carboxymethylcellulose (CMC) 1%) with 3 replications. The clear zone formed around the disc was measured using a caliper.Results : The results showed that there was no clear zone formed around the disks of the n-hexane extract of Malacca leaves. It can be concluded that the n-hexane extract of Malacca leaves could not inhibit the growth of Microsporum canis.Conclusion: The findings of this study indicate that the n-hexane extract of Malacca leaves, at concentrations of 25%, 50%, and 75%, does not exhibit antifungal activity against Microsporum canis in vitro, as evidenced by the absence of inhibition zones. Therefore, n-hexane may not be an effective solvent for extracting antifungal compounds from Malacca leaves against this fungal species.